Evaluating avoidance distance and fleeing speed of broilers exposed to aerial systems - Parajuli, Pratik; Zhao, Yang; Tabler, Tom (International Journal of Agricultural and Biological Engineering, 2020)
Intensive labor chores for broiler production could be reduced by using automated systems. However, broilers’ response toward automated systems remains unclear. The experiments were conducted to determine the avoidance distance (AD) and the fleeing speed (FS) of 4-8 weeks old broilers toward two aerial systems, a rail with a dummy arm and a drone, operated at different speeds (0.2-1.2 m/s), and heights (0.3-1.8 m) in a commercial broiler house. The broiler AD to a human assessor was also determined for comparison. Results show that the overall mean and standard error (SE) of broiler AD were 63±3 cm for the assessor, 58±1 cm for the rail, and 85±1 cm for the drone. As bird age increased from week 4 to week 8, broiler AD reduced significantly from 82 to 45 cm for the rail but showed no significant change for the drone. As the operational speed increased, broiler AD significantly increased from 54 cm (0.2 m/s) to 62 cm (0.4 m/s) for the rail, and from 81 cm (0.4 m/s) to 89 cm (1.2 m/s) for the drone. As the operational height increased, broiler AD increased from 54 cm (0.3 m) to 57 cm (1.5 m) for the rail and 81 cm (1.2 m) to 88 cm (1.8 m) for the drone. Overall mean and SE of broiler FS were 0.21±0.01 m/s for the rail and 0.65±0.01 m/s for the drone. As bird age increased from week 4 to week 8, the mean broiler FS decreased from 0.47 to 0.07 m/s for the rail and from 0.84 to 0.16 m/s for the drone. Increasing operational speed from 0.2 to 0.4 m/s for the rail and from 0.4 to 1.2 m/s for the drone significantly increased the mean FS from 0.18 to 0.24 m/s and from 0.52 to 0.78 m/s, respectively. Increasing the height of the rail from 0.3 to 1.5 m decreased the broiler FS from 0.27 to 0.16 m/s. However, increasing drone height from 1.2 to 1.8 m retained a similar FS. The outcomes of this study can help to better understand the interaction of broilers with aerial systems and provide insights into the optimization of robotic operational strategies while maintaining good broiler welfare production. Keywords: aerial automated system, avoidance distance, broiler, drone, fleeing speed DOI: 10.25165/j.ijabe.20201306.5591 Citation: Parajuli P, Zhao Y, Tabler T. Evaluating avoidance distance and fleeing speed of broilers exposed to aerial systems. Int J Agric & Biol Eng, 2020; 13(6): 34–40.